BETWEEN PAST AND FUTURE: QUEBEC EDUCATION IN TRANSTION. (Authors: Norman Henchey and Donald A. Burgess) - LeBlanc, André E. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1988)
Norman Henchey and Donald A. Burgess. BETWEEN PAST AND FUTURE: QUEBEC EDUCATION IN TRANSTION. Calgary: Detselig Enterprises Ltd., 1987. 294 pp. 21.95.